THE CORRELATION BETWEEN GRAMMAR MASTERY AND WRITING ABILITY (A CORRELATION STUDY) AT THE TENTH GRADE OF SMK NEGERI 1 SIBORONGBORONG - Vera Nadeak; Bonari H Tambunan; Rotua Hutasoit; Juandi Nababan (LPPM Universitas Darma Agung, 2021)
The purpose of this study is to know whether there is a significant correlation between grammar mastery and writing ability at the Tenth Grade of SMK Negeri 1 Siborongborong. The sample of this study is 30 students taken from B class of six. The method used in this study was a quantitative method and the technique used in this study was a correlational technique. In collecting the data, the documentation of students‟ writing scores and the test of grammar are used. The scores of writing were collected from the learning Process of writing subject at Tenth Grade of SMK Negeri 1 Siborongborong. Besides, in assessing students‟ mastery of grammar, this study conducted multiple choice and error identification test to the students. The result of this study shows that there is a very low correlation between students‟ grammar mastery and writing ability. It is proved by the rxy (0.165) is lower than rtable in the degree of significance 5% (0.374) and 1% (0.478). It is considered that the null hypothesis (Ho) is accepted and the alternative hypothesis (Ha) is rejected.